Towards a Migrant-Centred Perspective on International Migration: The Contribution of Amartya Sen's Capability Approach - Sara Bonfanti (Social Work and Society)
Cross-border migration, a multifaceted phenomenon involving a heterogeneous population all over the world, is studied by a fragmented host of theories. Departing from a critical review of economic neo-classical theories, this paper proposes a model which is able to overcome some of the pitfalls of such approaches to migration and to bring to the forefront migration as a fundamental capability whose impact on migrants' well-being depends on the interconnection between structural phenomena and migrants' agency. This is achieved by combining the explanatory power provided by an integrated reading of the main existing theories about international migration with the theoretical tools offered by the Amartya Sen' capability framework and the findings of the migration-related literature recently developed within the HDCA scholarship. A discussion of the most suited methods to operationalize such framework concludes the paper.